Middle-Upper Triassic and Middle Jurassic tetrapod track assemblages of southern Tunisia, Sahara Platform. (May 2017) - Niedźwiedzki, Grzegorz; Soussi, Mohamed; Boukhalfa, Kamel; Gierliński, Gerard D.
Abstract: Three tetrapod track assemblages from the early-middle Mesozoic of southern Tunisia are reported. The strata exposed at the Tejra 2 clay-pit near the Medenine and Rehach site, located in the vicinity of Kirchaou, contain the first tetrapod tracks found in the Triassic of Tunisia. The Middle Jurassic (early Aalenian) dinosaur tracks are reported from the Mestaoua plain near Tataouine. In the Middle Triassic outcrop of the Tejra 2 clay-pit, tridactyl tracks of small and medium-sized dinosauromorphs, were discovered. These tracks represent the oldest evidence of dinosaur-lineage elements in the Triassic deposits of Tunisia. Similar tracks have been described from the Middle Triassic of Argentina, France and Morocco. An isolated set of the manus and pes of a quadrupedal tetrapod discovered in Late Triassic Rehach tracksite is referred to a therapsid tracemaker. The Middle Jurassic deposits of the Mestaoua plain reveal small and large tridactyl theropod dinosaur tracks (Theropoda track indet. A-C). Based on comparison with the abundant record of Triassic tetrapod ichnofossils from Europe and North America, the ichnofauna described here indicates the presence of a therapsid-dinosauromorph ichnoassociation (without typical Chirotheriidae tracks) in the Middle and Late Triassic, which sheds light on the dispersal of the Middle-Upper Triassic tetrapod ichnofaunas in this part of Gondwana. The reported Middle Jurassic ichnofauna show close similarities to dinosaur track assemblages from the Lower and Middle Jurassic of northwestern Africa, North America, Europe and also southeastern Asia. Sedimentological and lithostratigraphic data of each new tracksite have been defined on published data and new observations. Taken together, these discoveries present a tantalizing window into the evolutionary history of tetrapods from the Triassic and Jurassic of southern Tunisia. Given the limited early Mesozoic tetrapod record from the region, these discoveries are of both temporal and geographic significance. Highlights: New tetrapod tracksites from Mesozoic of Tunisia are reported. Middle-Late Triassic assemblages contain dinosaurian ichnotaxa. Middle Jurassic ichnofauna shows similarity to dinosaur track assemblages from Africa, Europe and Asia. These trace fossils represent the first tetrapod finds in the Triassic of Tunisia.